Intubating laryngeal airway vs. direct laryngoscope: a crossover randomized controlled neonatal manikin trial - Chiara Monfredini; Francesco Cavallin; Paul Ouedraogo; Leila Ezzahraoui; Elisa Pasta; Daniele Trevisanuto; Paolo Ernesto Villani (Italian Journal of Pediatrics)
Abstract Background We aimed to compare endotracheal intubation through a laryngeal mask vs. using a direct laryngoscope in a manikin simulating a term infant. Methods A randomized, controlled, crossover (AB/BA) trial of intubation through a laryngeal mask vs. a direct laryngoscope in a manikin simulating a term infant. Thirty-four tertiary neonatal intensive care unit consultants and pediatric residents who had previous experience with intubating laryngeal airway and direct laryngoscopy participated. The primary outcome measure was the success of the procedure at the first attempt. The secondary outcome measures included the total time of endotracheal tube positioning and participant’s opinion on insertion difficulty and overall difficulty. Results Success at first attempt was 34/34 with the laryngeal mask (100%) and 26/34 with the direct laryngoscope (76%) (difference in percentage 24%, 95% confidence interval 5–41%; p = 0.008). Median time of endotracheal tube positioning was 24 s (IQR 19–30) with both devices (p = 0.86). Insertion difficulty (p = 0.96) and overall difficulty (p = 0.99) were not statistically different between the devices. Conclusions In a term infant manikin model, positioning the endotracheal tube through the laryngeal mask increased the success at the first attempt compared to direct laryngoscopy, without extending the duration of the procedure or affecting the perceived difficulty. Registration clinicaltrial.gov NCT06263790. Registered 16 February 2024, https://clinicaltrials.gov/study/NCT06263790 .